2020
DOI: 10.1155/2020/2067959
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen- and Stress-Activated Protein Kinase 1 Mediates Alcohol-Upregulated Transcription of Brf1 and tRNA Genes to Cause Phenotypic Alteration

Abstract: Upregulation of Brf1 (TFIIB-related factor 1) and Pol III gene (RNA polymerase III-dependent gene, such as tRNAs and 5S rRNA) activities is associated with cell transformation and tumor development. Alcohol intake causes liver injury, such as steatosis, inflammation, fibrosis, and cirrhosis, which enhances the risk of HCC development. However, the mechanism of alcohol-promoted HCC remains to be explored. We have designed the complementary research system, which is composed of cell lines, an animal model, human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Emerging studies have clearly demonstrated that alcohol consumption is an established risk factor for breast cancer [ 22 25 ]. Approximately 80% of all cases of breast cancer are ER+ (estrogen receptor-positive) and 20% ER- (estrogen receptor-negative) [ 1 , 2 , 10 ]. Alcohol intake is associated with ER+ cases of breast cancer more than ER- cases [ 1 ].…”
Section: Alcohol-induced Deregulation Of Brf1 and Pol III Genes And Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging studies have clearly demonstrated that alcohol consumption is an established risk factor for breast cancer [ 22 25 ]. Approximately 80% of all cases of breast cancer are ER+ (estrogen receptor-positive) and 20% ER- (estrogen receptor-negative) [ 1 , 2 , 10 ]. Alcohol intake is associated with ER+ cases of breast cancer more than ER- cases [ 1 ].…”
Section: Alcohol-induced Deregulation Of Brf1 and Pol III Genes And Breast Cancermentioning
confidence: 99%
“…Deregulation of Brf1 and Pol III genes is tightly linked to cell proliferation, cell transformation, and tumor development [ 4 9 ]. Brf1 is overexpressed in several human cancers, such as hepatocellular carcinoma, breast cancer, gastric cancer, prostate cancer, and lung cancer [ 5 , 8 , 10 13 ], while carcinogens, such as EGF (epidermal growth factor), DEN (Diethylnitrosamine), and MNNG (N-methyl-N′-nitro-N-nitrosoguanidine), and dietary factors (alcohol) induce the deregulation of Brf1 and Pol III genes [ 4 , 7 , 10 , 13 , 14 ]. This shows that the deregulation of Brf1 and Pol III genes plays a critical role in tumor development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E1910). The luciferase activities of the lysates were normalized to their protein amounts as described [ 31 , 32 ]. The changes in luciferase activity were compared to the luciferase activity in the absence of MNNG.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies have demonstrated that alcohol increases Brf1 expression in tissue culture and animal models, which facilitates cell proliferation and transformation, and tumor formation [15,17,19,20,[29][30][31][32]. Chronic alcohol consumption results in the production of acetaldehyde and CYP2E1 induction (Cytochrome P450 2E1) [14].…”
Section: Introductionmentioning
confidence: 99%